Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00335-016-9661-8
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of Down syndrome: gene content and consequences

Abstract: Down syndrome (DS), trisomy of human chromosome 21 (Hsa21), is challenging to model in mice. Not only is it a contiguous gene syndrome spanning 35 Mb of the long arm of Hsa21, but orthologs of Hsa21 genes map to segments of three mouse chromosomes, Mmu16, Mmu17 and Mmu10. The Ts65Dn was the first viable segmental trisomy mouse model for DS; it is a partial trisomy currently popular in preclinical evaluations of drugs for cognition in DS. Limitations of the Ts65Dn are: (i) it is trisomic for 125 human protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
156
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(163 citation statements)
references
References 149 publications
(161 reference statements)
0
156
0
Order By: Relevance
“…Hsa21 contains 222 protein coding genes, and 325 non‐protein encoding genes . Studies of partial trisomy of Hsa21 have revealed that multiple regions of Hsa21 contribute to the observed physical and neurodevelopmental characteristics of Down syndrome .…”
Section: Individual Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Hsa21 contains 222 protein coding genes, and 325 non‐protein encoding genes . Studies of partial trisomy of Hsa21 have revealed that multiple regions of Hsa21 contribute to the observed physical and neurodevelopmental characteristics of Down syndrome .…”
Section: Individual Variabilitymentioning
confidence: 99%
“…Mouse models of Down syndrome have been crucial to help investigate the genetic and developmental origins of the Down syndrome phenotype and importantly to test therapies that have the potential to improve neurogenesis and long‐term cognition . Hsa21 shares synteny with a large proportion of mouse chromosome (Mmu) 16 (approximately 102 protein coding genes) and shorter regions of Mmu10 (37 protein coding genes) and Mmu17 (19 protein coding genes) . These have all been key targets in generating mouse models of Down syndrome (for a comprehensive list of mouse models of Down syndrome see Herault et al …”
Section: Mouse Models Of Down Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…2) Down syndrome is caused by a triplication of chromosome 21, incorporating a third copy of approximately 300 genes (Holtzman and Epstein 1992; Hattori et al, 2000; Chapman et al, 2000; Gardiner et al, 2010; Dierssen, 2012; Kleschevnikov et al, 2012). Ts65Dn mice with partial trisomy of the syntenic genes on mouse chromosome 16, originally generated by Reeves, Davisson and co-workers (Reeves et al, 1995), display behavioral abnormalities including deficits in water maze hidden platform acquisition, novel object recognition and radial maze, and higher exploration in an open field and on an elevated plus-maze (Reeves et al, 1995; Coussons-Read and Crnic, 1996; Demas et al, 1996; Sago et al, 2000; Moran et al, 2002; Martinez-Cue et al, 2005; Costa et al, 2010; Das and Reeves, 2011; Braudeau et al, 2011; Cramer and Galdzicki, 2012; Velazquez et al, 2013; Smith et al, 2014; Gupta et al, 2016). 3) Rett syndrome is caused by a mutation in MECP2 on the X chromosome, which codes for the epigenetic methylation regulator methyl-CpG-binding protein (Amir et al, 1999; Lombardi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Gardiner reviewed the gene content of HSA21, emphasizing what is now known about long noncoding RNA genes and the conservation of protein-coding genes in orthologous mouse genomic regions [Gupta et al, 2016]. She also presented new data on the extensive differences in protein expression in several brain regions between male and female DS mice trisomic for the HSA21 orthologous region on mouse chromosome 10 (MMU10).…”
mentioning
confidence: 99%